Quality assurance in civil engineering one day seminar, Thursday 30 April 1987, 9:30 am at the Donnington Thistle Hotel, East Midlands Airport, Junction 24 M1 : ICE approved for one day PE1 and PE2. (Thomas Telford, 1987)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a one-day seminar held in Donington in 1987.